(-8x)-2x=0

Simple and best practice solution for (-8x)-2x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-8x)-2x=0 equation:


Simplifying
(-8x) + -2x = 0

Combine like terms: (-8x) + -2x = -10x
-10x = 0

Solving
-10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-10'.
x = 0.0

Simplifying
x = 0.0

See similar equations:

| 244=-8(1+5x)-8 | | 5s-2+3(5-11)=5 | | 1.6y=6 | | (r^2-20tw)= | | -x^2+23x-132=0 | | 9x^2+11x+18=0 | | 18f=126*3 | | 5(20x-40)=48 | | 9x^2+11x+8=0 | | 8w-35=3w | | 3d=3.6*2.5 | | r^2-20tw= | | y=4.2-2.8x | | x^2+61=12x | | 9+7x=6x+19 | | 8x+6y=16 | | 19c=5*57 | | f+(+60)+(2f-50)+3f=1424 | | 5x(5x+3)=19 | | 8(2x+3)-1= | | M-6+6=-2 | | -7-(-18)+(-10)= | | 27x^3+72x^2+48x=0 | | 1.9=2.9-0.2x | | (4x+1)+(6x-5)= | | -384=6(1-13x) | | 0.5*t=5*0.3 | | 5x(5x+3)=18 | | 6*0.5=-4(n-1) | | 0.25+15=7 | | -4x^2=224 | | .33+.66m=.66-.66 |

Equations solver categories